Development of adsorbents from municipal sewage sludge - Chen, Xiaoge. (2008)
Disposal of sewage sludge is an increasingly expensive and environmentally sensitive problem throughout the world. Preparation of carbonaceous adsorbents from sewage sludge offers an attractive re-use alternative to the traditional disposal routes. This approach is consistent with the concept of sustainable technology and waste minimisation that is receiving much attention at present throughout the world, particularly in industrialised and densely populated areas.